Structural modelling of collective action behavior of farmers for natural resource management - PRIYADARSHNI, PRITI; PADARIA, R N; BURMAN, R R; SINGH, RASHMI; BANDYOPADHYAY, SANJOY; KUMAR, PRAMOD; BHOWMIK, ARPAN; SHARMA, ROMEN (The Indian Journal of Agricultural Sciences, 2022)
Community engagement is a crucial element for effective management of natural resources. This study is aimed at determining the factors and analyzing their path for collective action behavior of farmers towards natural resource management. Two cases of community based natural resource management were conducted in Phek and Kohima districts of Nagaland during 2020 and with thematic their analysis of activities, the probable factors of collective action among the communities were listed. Through participatory rural appraisal, focus group discussion and personal interview method data, was collected with a total sample size of randomly selected 106 farmers. The composite reliability for the explanatory variables, viz. social cohesiveness, normative belief, collective action for resource management, trust, community orientation, social relationship, and shared values were 0.79, 0.81,0.92, 0.6, 0.72, 0.78, and 0.52, respectively. Exploratory factor analysis resulted in 7 factors with 63.7% of the total variance explained. The obtained factors were validated through measurement modelling by confirmatory factor analysis. The structural model had goodness of fit with acceptable values of RMSEA (0.09), GFI (0.96) and CFI (0.92). The relationship of community orientation was found highly significant with normative belief (Z=6.36**); social cohesiveness (2.27**) and collective action (Z=3.47**). Emphasis should be laid upon promotion of normative beliefs, local institutions, and social values for augmentation of collective action for natural resource management.